Factors Affecting the Reading Abilities of Grade 7 Learners, Basis for an Action Plan - Diga, Marivic A. (Future Science / FSH-PH Publications, 2023)
This study determined the factors affecting the reading abilities of Grade 7 learners of Castillejos Resettlement High School, Castillejos District, Schools Division of Zambales for the School Year 2022. The implemented distance learning modality was a great challenge in the teaching-learning process because of the limited assistance and guidance of teachers as the main facilitator in learning. After two academic years, when distance learning modality was implemented due to the Covid 19 Pandemic, the school year opened last August 22, 2022 with full implementation of in-person classes and schools have conducted reading pre-tests and screening tests with the use of Phil IRI (Philippine Informal Reading Inventory). The results in the conducted reading pre-test and group screening test pressed the necessity to find out the factors affecting the reading abilities of students in Grade 7 at Castillejos Resettlement High School. The researcher utilized a descriptive quantitative method of research and conducted a research questionnaire in gathering data as instrument which included respondents’ profile and perception of the learner- related factors, teacher-related factors and school-related factors. Likert scale, frequency and percentage distribution, Pearson Correlation Coefficient r and mean were used to scale the gathered data. The results revealed that the respondents, in general, strongly agreed that learner-related factors, teacher-related factors and school-related factors affected their reading abilities. Hence, there was negatively low non-significant correlation between the reading abilities and the factors affecting the reading abilities among students in terms of learner-related factors, teacher-related factors and school-related factors.